Implementasi Supervisi Akademik melalui Pemanfaatan CCTV sebagai Upaya Monitoring Jarak Jauh terhadap Kinerja Guru di MAN 1 Kuantan Singingi pada Semester Ganjil Tahun Pelajaran 2022/2023 - Suhelmon, Suhelmon (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This study aims to obtain a clear picture of the academic supervision that has been carried out at MAN 1 Kuantan Singingi in an effort to remotely monitor teacher performance. This research was conducted for 4 weeks in August to. September 2022. The research stages were carried out based on the process guidelines in management. Management is a series of processes that include planning, organizing, implementing, supervising, evaluating and controlling activities in order to empower all organizational/company resources, both human resources (human resource capital), capital (financial capital), materials (land, natural resources or raw materials), and technology optimally to achieve organizational/company goals (Pratama, 2020), the organization in question in this case is MAN 1 Kuantan Singingi. The research subjects were selected using random sampling technique. The subjects were 6 different homeroom teachers, to obtain a variety of data from different rombel. Consisting of 1 homeroom teacher X MIPA 5, 1 homeroom teacher X IPS 2, 1 homeroom teacher X PK 1, 1 homeroom teacher XI MIPA 4, 1 homeroom teacher XI IPS, and 1 homeroom teacher XI PK 1. The object of this research is teacher performance. The research data were obtained from observation and documentation of CCTV results during supervision/monitoring of teachers. The analysis technique used in this research is qualitative analysis. According to Arikunto (2006), qualitative research is research on research that is descriptive and tends to use analysis (Sudaryono, 2016). The results showed that the use of CCTV in the implementation of monitoring teacher performance at MAN 1 Kuantan Singingi was in a good category